A conceptual model of interactive museum exhibition for intangible Dongba Cultural Heritagens - Wen, Yang (2025)
The traditional display methods in the Dongba culture museums often fail to present the richness and complexity of this unique culture. Their non-interactive display forms fail to attract modem audiences, especially the younger generation. While numerous studies focus on interactive museum exhibitions for tangible heritage artifacts, it is found that a lack of a conceptual model for interactive museum exhibitions tailored to intangible cultural heritage. Therefore, taking Lijiang Dongba Cultural Museums as a case study, this thesis introduces a conceptual model for interactive museum exhibition for intangible Dongba cultural heritage. The study objectives are: (i) to identify the main components of online and offline interactive museum exhibitions suitable for intangible Dongba cultural heritage, (ii) to develop a conceptual model of interactive museum exhibition for intangible Dongba cultural heritage, and (iii) to validate the conceptual model of interactive museum exhibition for intangible Dongba cultural heritage. The design science research methodology is adapted, involving a preliminary study of 126 respondents to identify the main components of online and offline interactive museum exhibitions, justified with literature prior to designing the conceptual model. An expert review is conducted with seven experts to verify the model. User evaluation garnered 123 participants, where all components of the conceptual model for interactive museum exhibition are found acceptable and able to provide educational content, interactivity, and satisfaction, in that order, to the users. This conceptual model serves as guidelines for museum directors and interactive museum exhibition developers to embrace both online and offline interactive museum exhibitions for intangible cultural heritage at large